Evaluation of Quantitative Coronary Angiography for Assessment of Adequacy of Stent Deployment - Ali, jabar; Khan, Iftikhar Ahmad; Irfan, Mohammad; Khan, Abdul Wali; Wazir, Bughdad Wazir (International Journal of Pathology, 2018)
Objective: To determine the adequacy of stent symmetry (deployment) as assessed by intravascular ultrasound(IVUS) and its comparison with quantitative coronary angiography (QCA).Methodology: In this comparative study we analyzed the stents for adequate deployment in 100 patients whowere randomly selected from the patients who were undergoing percutaneous coronary angiography (PCI) eitherwith bare metal or drug eluting stent at our catheterization laboratory, Cardiology department Postgraduate MedicalInstitute (PGMI) Lady Reading Hospital Peshawar. The study was conducted from August 2010 to February2011. We used Volcano therapeutic intravascular ultrasound (IVUS) system employing Volcano – eagle eye Goldcatheter. Stents was supposed to be symmetrical (adequately deployed) if the ratio of minimum luminal diameterto maximum luminal diameter was 0.7.Performa was used to collect patient’s details and record the IVUS analysis.Statistical Package for the Social Sciences SPSS version 15 was used to analyze the data.Results: A total of 100 subjects were included in the study, their mean age was 54.38 ± 9.97 years and 85 %( 85)were male. Diabetics were 40 %(40), hypertensive’s were 47%(47), dylipidemic were 46%(46) smokers were 36%(36)and 40%(40) had a previous myocardial infarction. Both drug eluting and bare metal stents were used and themain drug eluting stent was endeavor (Zatrolimus eluting stent) and the main bare metal stent was integrity.Left anterior descending artery (LAD) was most commonly stented artery, followed by circumflex and right coronaryartery respectively.Mean ratio of the minimum to maximal luminal diameter was 0.8205 ± 0.084. A ratio of greater than 0.7 wasachieved in 77.5% patients so that they had a better symmetry.By quantitative coronary angiography (QCA) only 5% of the stented lesions were having greater than 10% residualstenosis not properly deployed while 95% of the stents were adequately deployed. When we compared our findingof IVUS with that of quantitative coronary angiography( QCA )by applying chi-square test, we found that therewere significant stents that were not properly deployed (p valve of 0.00312) and need further dilatation.Conclusion: In significant number of patients stents were not adequately deployed requiring re-ballooning tooptimize the results as assessed by intravascular ultrasound (IVUS).